Investigating the use of sodium silicate to improve the flotation performance of Platreef and UG2 PGE ores - Nyaruwata, Everjoice (Department of Chemical Engineering, 2024)
The Bushveld Igneous Complex (BIC) in South Africa is one of the largest platinum group minerals (PGM) depositories in the world. Due to the depletion in high grade ores, there has been a shift to processing low grade, mineralogically complex, finely disseminated and often altered ores. These ores require fine grinding to sufficiently liberate the very fine grained PGMs which subsequently liberates the very fine phyllosilicate gangue minerals; namely serpentine and talc. The presence of these minerals poses three major problems to valuable mineral recovery. Firstly, serpentine slimes may form a hydrophilic layer on the valuable mineral surface leading to a decrease in recovery. Secondly, serpentine and talc may form homo-coagulants that can increase the pulp viscosity and also result in a decrease in recovery. Lastly, the presence of naturally floating gangue such as talc can be recovered via true flotation and hence lower the concentrate grade. The widespread mitigation methods in commodities other than PGM's, involve use of dispersants to reverse slime coating, use of rheology modifiers to lower pulp viscosity and depressants to hinder the recovery of naturally floating gangue. All these methods target the problems individually. Sodium silicate has been previously observed to effectively address all three problems simultaneously in a highly altered PGE ore thereby enhancing flotation performance. Therefore, there is a need to assess sodium silicate performance on moderately altered to relatively unaltered PGE ores, where there is no published data in this regard. To assess how sodium silicate influences the flotation response of Platreef ore, batch flotation tests were performed at five different sodium silicate dosages in the range 0 g/t (baseline condition) to 2000 g/t sodium silicate on the secondary grind (80% passing 45 µm) using sodium metasilicate of modulus 1. For comparison purposes, batch flotation tests were also performed on the UG2 secondary grind (80% passing 45 µm) and Platreef primary grind (48% passing 75 µm) at 0 g/t and 2000 g/t sodium silicate. Additional batch flotation tests were conducted with variable moduli in the range 1 – 3 at a constant sodium silicate dosage to assess the effect of modulus on Platreef ore. Due to the pH modification properties of sodium silicate, batch flotation tests were conducted at an equivalent pH as 2000 g/t sodium silicate, without adding sodium silicate, to decouple the pH effects. Supplementary rheology and froth stability experiments were performed on both Platreef and UG2 secondary grinds to further assess sodium silicate activity. Characterization measurements such as quantitative evaluation of minerals by scanning electron microscopy (QEMSCAN) and qualitative X-ray diffraction (QXRD) were also performed on the Platreef and UG2 feed samples and Platreef concentrates to obtain the PGM characterization and bulk modal mineralogy data. The bulk modal mineralogy data showed that the Platreef and UG2 ores contain 16.4 weight percent (wt%) and 4.5 wt% alteration minerals, respectively. The four minerals being categorised as alteration minerals are serpentine, chlorite, amphibole and talc. Therefore, Platreef was expected to exhibit more detrimental effects on mineral recovery than UG2. Batch flotation tests revealed that high dosages (2000 g/t) of sodium silicate enhanced both Pt and Pd grades and recoveries in a Platreef ore. The high sodium silicate dosages also improved the rheological environmental by lowering the pulp viscosity and improved froth drainage. It was believed that slime coating reversal and a reduction in slurry viscosity which improved gas dispersion and bubble-particle interactions were responsible for the recovery enhancements. The grade improvements were attributed to the depression of talc and talc-composite particles, as well as improved froth drainage, leading to lower entrainment. QEMSCAN analysis revealed that sodium silicate mainly improved the recovery of PGE sulphides and PGE tellurides. These are believed to have been responsible for the recovery gains reported. However, sodium silicate appeared to negatively impact the floatability of PGE arsenides. The Platreef concentrates at 0 g/t and 2000 g/t sodium silicate were also split into three size fractions (-10 µm, +10 – 38 µm and +38 µm) and the recovery-by-size data showed a significant increase in the Pt and Pd recovery of the +38 µm size fraction. This was attributed to the slime cleaning effect of sodium silicate. These findings were supported by the PGM particle size distribution as it showed an increase in the amount of coarser particles at 2000 g/t sodium silicate. The modulus tests also revealed that the higher modulus had very little effect on the recovery but significantly lowered the concentrate grades. This was attributed to increased entrainment and the polymerization effect of sodium silicate at higher modulus which might have hindered the depression of naturally floating gangue. The pH tests revealed that high pH can improve Pt and Pd recoveries but at the expense of grade. This showed that high pH had no effect on talc depression. Also, the recovery enhancements at the higher pH were lower than that at high sodium silicate dosage. It was postulated that the recovery improvements were a result of both an increase in solids recoveries and the removal of slime coatings as hydroxide ions are capable of reversing mineral surface charge of the alteration minerals. A comparison between the flotation performance of the Platreef primary and secondary grinds showed that the primary grind experienced a higher concentrate upgrade than the secondary grind, although only the secondary grind experienced recovery improvements. This was expected, due to the more problematic nature of finer particle sizes, which the addition of sodium silicate is able to mitigate. It can therefore be concluded that addition of sodium silicate at the primary grind is not effective or required. A comparison between the Platreef and UG2 performance showed that sodium silicate also upgraded the UG2 concentrates, reduced the pulp viscosity and improved froth drainage, but slightly reduced the PGE recoveries. The grade improvements were also attributed to talc depression and reduced recovery of entrained gangue minerals. These findings show that Platreef is more amenable to sodium silicate than UG2 since it experienced both grade and recovery enhancements. It was postulated that the higher concentration of alteration minerals in Platreef pose a greater negative effect on flotation performance, which can be mitigated by sodium silicate addition. Therefore, the outcomes of this study revealed the dispersant, rheology modification and depressant properties of sodium silicate on a moderately altered ore as reflected by the grade and recovery enhancements and shows promise for usage as a single method for combating the three major problems associated with alteration minerals in Platreef ore. It further showed that its use is not required for coarser grinds or for ores with less alteration minerals present. Low modulus is better for both grade and recovery improvements and high pH is not an alternative to sodium silicate addition.